Mobile Connectivity: Ubiquitous Learning with Web-Based Module to Promote Scientific Argumentation Skills in Science Learning - Fatma, Elisa; Supeno, Supeno; Nuha, Ulin (Jurnal Pendidikan MIPA, 2024)
Argumentation skills are still a challenge in science learning. Teachers must develop innovative learning to promote various thinking skills, one of which is argumentation skills. This research aims to develop valid, practical, and effective modules based on the web. The type of research applied was educational development research (EDR) with the ADDIE development model. The data collection techniques and instruments include validation sheets, practicality sheets, tests, observations, interviews, questionnaires, and documentation. The research sample was class VIII-B SMPN 1 Sukowono, with 26 students. The data analysis results of the validity of the modules based on the web got an average score of 85% with highly valid criteria. The results of the learning implementation analysis got an average score of 85%, which is an outstanding category from the assessment of the three observers. Product effectiveness is obtained from test results and student response questionnaire sheets. The results of the product effectiveness analysis using the N-Gain test got an average score of 0.74 in the high criteria. Students can learn in various places and situations by accessing modules and collaborating with other students and other learning resources available on the network. Thus, the web-based module is feasible for improving argumentation skills.         Keywords: ubiquitous learning, web-based module, argumentation skills, science learning. DOI: http://dx.doi.org/10.23960/jpmipa/v25i1.pp386-398